Microgram amounts of abscisic acid in fruit extracts improve glucose tolerance and reduce insulinemia in rats and in humans. Issue 12 (4th August 2015) - Magnone, Mirko; Ameri, Pietro; Salis, Annalisa; Andraghetti, Gabriella; Emionite, Laura; Murialdo, Giovanni; De Flora, Antonio; Zocchi, Elena
ABSTRACT: 2‐ Cis, 4‐ trans ‐abscisic acid (ABA) is a plant hormone that is present also in animals. Several lines of evidence suggest that ABA contributes to the regulation of glycemia in mammals: nanomolar ABA stimulates insulin release from β‐pancreatic cells and glucose transporter‐4‐mediated glucose uptake by myoblasts and adipocytes in vitro ; plasma ABA increases in normal human subjects, but not in diabetic patients, after a glucose load for an oral glucose tolerance test (OGTT). The presence of ABA in fruits prompted an exploration of the bioavailability of dietary ABA and the effect of ABA‐rich fruit extracts on glucose tolerance. Rats underwent an OGTT, with or without 1 μg/kg ABA, either synthetic or present in a fruit extract. Human volunteers underwent an OGTT or a standard breakfast and lunch, with or without a fruit extract, yielding an ABA dose of 0.85 or 0.5 μg/kg, respectively. Plasma glucose, insulin, and ABA were measured at different time points. Oral ABA at 0.5–1 μg/kg significantly lowered glycemia and insulinemia in rats and in humans. Thus, the glycemia‐lowering effect of low‐dose ABA in vivo does not depend on an increased insulin release. Low‐dose ABA intake may be proposed as an aid to improving glucose tolerance in patients with diabetes who are deficient in or resistant to insulin.—Magnone, M., Ameri, P., Salis, A., Andraghetti, G., Emionite, L., Murialdo, G., De Flora, A., Zocchi, E. Microgram amounts of abscisic acid in fruit extracts improve glucose tolerance and reduce insulinemia in rats and in humans. FASEB J. 29, 4783–4793 (2015). www.fasebj.org